Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT Fresh One SJS Jakarta Barat - Puspa Wira Santi; Iman Syatoto; Sunardi Sunardi; Reni Hindriari (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The workplace environment and work discipline are important factors influencing employee performance at PT Fresh One SJS Jakarta Barat This study examines how both variables contribute to performance improvement within the organization. This research aims to analyze the effect of work environment and work discipline on employee performance at PT Fresh One SJS Jakarta Barat. This study uses a quantitative approach with an associative research design The population consists of 90 employees all of whom were selected using a census sampling technique Data were collected through a Likert-scale questionnaire The data were processed using SPSS version 25 and analyzed using multiple linear regression. The findings indicate that both work environment and work discipline have a positive and significant effect on employee performance both partially and simultaneously The model shows that improvements in the work environment and discipline lead to higher employee productivity and effectiveness These results suggest that organizations should improve workplace conditions and strengthen disciplinary policies to enhance employee performance and achieve organizational goals effectively Overall both variables are essential determinants of performance improvement in the company context in Jakarta Barat area Indonesia.